Description of larvae of Japanese Macronychini (Coleoptera: Elmidae: Elminae) - Hayashi, Masakazu; Kamite, Yuuki (Zootaxa, 2020)
Larvae of 15 species of Macronychini, subfamily Elminae, belonging to the genera Sinonychus Jäch & Boukal, Paramacronychus Nomura, Zaitzeviaria Nomura, Zaitzevia Champion, and Urumaelmis Satô were described based on scanning electron microscope (SEM) observation. Larvae of eleven of these species, S. tsujunensis Yoshitomi & Nakajima, Zaitzeviaria gotoi (Nomura), Zaitzeviaria brevis (Nomura), Zaitzeviaria kuriharai Kamite, Ogata & Satô, Zaitzevia elongata Nomura, Zaitzevia aritai Satô, Zaitzevia yaeyamana Satô, Zaitzevia awana (Kôno), Zaitzevia nitida Nomura, Zaitzevia tsushimana Nomura, and U. uenoi (Nomura) are described for the first time.